Assessment of phenotypic variability among EEA INTA Pergamino sunflower lines: Its relationship with the grain yield and oil content - Dominguez, Matías (2021)
The aims of the present study were to assess the phenotypic diversity among 221 sunflower accessions of INTA Pergamino Sunflower Breeding Program, to obtain discriminant functions that allow the classification of new accessions in similar groups and to evaluate the relationship between genetic distance pairwise accessions and hybrid performance for grain yield and oil content. We used 19 quantitative descriptors to evaluate phenotypic and morphological variability. Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA) were used to evaluate simultaneously all the variables and to describe phenotypic variation patterns of the germplasm. The distribution of germplasm in the dendrogram did not follow a clear pattern with regard to the predefined groups. This study revealed the variability observed among the lines that form the INTA Pergamino breeding program despite the highly selective forces applied to obtain inbred lines that produce superior hybrids for the Argentinean sunflower area. This work demonstrates the need for more in-depth study of genetic variability to be used as a predictor of heterosis in sunflower.